Variability of fusion vergence measurements in heterophoria - Lança, Carla Costa (2016)
Purpose: The aims of this study were to compare fusional vergence measurements between orthophoria, esophoria, and exophoria, and to determine the strength of correlations between fusional convergence and divergence and angle of deviation. Methods and materials: A cross-sectional study was performed in children with best-corrected visual acuity of 0.0 LogMAR in either eye, compensated heterophoria within 10 prism diopters (PD), full ocular rotations, presence of fusional vergence, and stereopsis (60 seconds of arc or better). Fusional amplitudes were compared between orthophoric and heterophoric children. The fusion reserve ratio was determined as compensating vergence divided by alternating cover test. Results: Five hundred and thirty children (7.66±1.20 years) were recruited to this study. The most common heterophoria was exophoria (n=181, 34.2% for near; n=20, 3.8% for distance). Exophoric children had significant lower mean positive fusional vergences (exophoria-orthophoria: P=0.003; exophoria-esophoria: P=0.035) for near (19.54±5.23 base-out) compared with children with orthophoria (20.48±4.83 base-out) and esophoria (22.27±5.60 base-out). Smaller convergence fusion amplitudes were associated with larger angles of deviation at near (rs=-0.115; P=0.008) and lower fusion reserve ratios were associated with larger angles of deviation at distance (rs=-0.848; P<0.001) and at near (rs=-0.770; P<0.001). Conclusions: Exophoric children have reduced convergence break points when compared with orthophoric and esophoric children. Vergence measurements, taking into consideration the baseline heterophoria, give important information about the ability of the patient to increase their vergence demand and maintain ocular alignment.